Influence of Sodium Hypochlorite on Microleakage of Three-step Total-etch Bonding Agent with Different Solvents - Mansoreh Mirzaei; Hamid Kermanshah; Esmaeil Yassini; ladan Ranjbar Omrani; Mehdi Abassi; Nasrin Akhondi; Raziyeh Saniee (Islamic Dental Association of Iran, 2013)
Background and Aim: some recent research have reported increased stability in mechanisms of adhesion to dentin in remove of collagen fiber of the dentin surface.The aim of this study was to evaluate the effect of sodium hypochlorite in microleakage of three step total etch dental adhesives with different solvents .   Materials and Methods : this experimental study on 80 intact bovine incisor teeth,   were prepared class V cavities on buccal surface of teeth, box shap and all walls on enamel.  Then the specimens were randomly divided into eight groups (n=10).  NaOCl+etching+ SBMP (waterbase), NaOCl+etching+ All Bond2 (Acetonebase),   etching+ NaOCl+ SBMP, etching+ NaOCl+ All Bond2,, NaOCl+ SBMP, NaOCl+ All   Bond2, etching+ SBMP, etching+ All Bond2.   Then the cavities were restored using Z250 (3M) composite and Coltolux 75 light curing unit (350 mw/cm2). The specimens were thermo cycled for 1000 times on water baths of 5and 55oC. After thermocycling, the specimens were immersed in a 2 % aqueous solutions of basic fuchsin for 24 hours, then longitudinal section of each restoration was obtained and examined with a stereomicroscope for evaluation of micro leakage. The data were analyzed using kruskal-walis test and the mean of micro leakage of samples were compared by two- way ANOVA test .   Results: The findings showed that the higher rate of micro leakage was detected in hypo+Acid and lower rate of micro leakage was detected in Acid+hypo in different treatment method. The finding was different in hypo+Acid procedure, the higher rate of micro leakage was in SBMP. In hypo groups, the microleakage with ALL Bond 2 was higher than SBMP. In control groups, the microleakage with SBMP was higher than ALL Bond2 .   Conclusion: Application of Naocl before dentin etching for removal organic materials increase the rate of microleakage of All Bond2 , SBMP to that of control group .